Dynamics of NH3(CH2)2NH3 cation in perovskite layer crystal NH3(CH2)2NH3CuCl4 by M. (May 2020) - Lim, Ae Ran
Abstract: We replaced Pb with nontoxic Cu metal for lead-free perovskite solar cells and investigated their potential for solar cell applications. The ionic dynamics of the NH3 (CH2 )2 NH3 CuCl4 crystal are investigated as a function of temperature, with a focus on the role of the NH3 (CH2 )2 NH3 + cation. This investigation was conducted by 1 H and 13 C MAS NMR experiments. The contributions to the NMR chemical shifts are correlated to the distribution of the spin density in the ligand moiety. The 1 H NMR chemical shift for NH3 changes more significantly with the temperature than that for CH2 . This change in the cationic motion is enhanced at the N-end of the organic cation, which is fixed at the inorganic layer by N–H⋯Cl hydrogen bonds. In addition, the molecular motions are discussed in terms of the spin-lattice relaxation time, which reveal that the CH2 ion located in the middle of the N–C–C–N bond undergoes tumbling motion according to the Bloembergen–Purcell–Pound theory. Highlights: Lead-free perovskite solar cells. The ionic dynamics of the NH3 (CH2 )2 NH3 CuCl4 . Molecular dynamics by nuclear magnetic resonance.